2021
DOI: 10.3389/fbioe.2021.707098
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study on 3D Bioprinting of Microfat Constructs Towards Wound Healing Applications

Abstract: Chronic wounds affect over 400,000 people in the United States alone, with up to 60,000 deaths each year from non-healing ulcerations. Tissue grafting (e.g., autografts, allografts, and xenografts) and synthetic skin substitutes are common treatment methods, but most solutions are limited to symptomatic treatment and do not address the underlying causes of the chronic wound. Use of fat grafts for wound healing applications has demonstrated promise but these grafts suffer from low cell viability and poor retent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
4
1
Order By: Relevance
“…A recent study used a closed-loop fat processing system to prepare microfat clusters and mix them with methacrylate collagen (CMA) for bioprinting. 43 The microfat clusters contained a large number of adipocytes, oil, and stromal cells, which are very different from the focus of this study. To evaluate the effect of 3D-bioprinted biomimetic multilayer implants consisting of mFAECM and cells for wound healing in vivo, we prepared a full-thickness skin defect model in nude mice (Figure 6A).…”
Section: Biomimetic Multilayer Implants Promoted Cutaneous Wound Heal...contrasting
confidence: 57%
See 1 more Smart Citation
“…A recent study used a closed-loop fat processing system to prepare microfat clusters and mix them with methacrylate collagen (CMA) for bioprinting. 43 The microfat clusters contained a large number of adipocytes, oil, and stromal cells, which are very different from the focus of this study. To evaluate the effect of 3D-bioprinted biomimetic multilayer implants consisting of mFAECM and cells for wound healing in vivo, we prepared a full-thickness skin defect model in nude mice (Figure 6A).…”
Section: Biomimetic Multilayer Implants Promoted Cutaneous Wound Heal...contrasting
confidence: 57%
“…There has been no prior study on the direct application of adipose-derived, nonpepsin-digested ECM to the construction of skin substitutes by 3D bioprinting. A recent study used a closed-loop fat processing system to prepare microfat clusters and mix them with methacrylate collagen (CMA) for bioprinting . The microfat clusters contained a large number of adipocytes, oil, and stromal cells, which are very different from the focus of this study.…”
Section: Resultsmentioning
confidence: 93%
“…Schmitt et al mixed cryopreserved microfat tissue and methacrylated collagen to obtain a bioink. [83] The bioink was processed into a bath of gelatin microspheres [84] and was stabilized afterward by UV crosslinking for 1 min. The authors reported that also high densities of the microfat could be introduced to the collagen without deteriorating the printing quality.…”
Section: Biomedical Bioprinting Of Adipose Tissuementioning
confidence: 99%
“…When trauma occurs, the structural integrity of blood vessels is damaged, and a significant volume of blood leaks out of them, resulting in blood loss and harm to other organs that, in severe situations, can be fatal [41]. Normally, vasoconstriction occurs first after injury to slow blood flow [40,42,43]. Platelets are then activated to form a primary thrombus via an endogenous and exogenous coagulation cascade reaction.…”
Section: Haemostasismentioning
confidence: 99%